Draft Annual Plan for 1968-69 Nagaland - Planning Commission (Planning Commission, 1967)
The Third Five Year Plan was actually the first Plan for the State. No systematic planning nor execution of any scheme with definite long-term objectivity could be taken up due to the disturbed conditions and absence of proper machinery prior to the Third Plan period. Even the Third Five Year Plan could not be prepared in a comprehensive manner. In fact the schemes were- drawn up and implemented from year to year on the basis of Annual Plans.
Government of Nagaland, Planning and Coordination Department